Multiple criteria evaluation of buildings with emphasis on sustainability - Šaparauskas, Jonas (Journal of Civil Engineering and Management, 2003)
It this article the author discussed how buildings influence environment. The main sustainable buildings information sources' review was made briefly. There are guides, handbooks, guidelines, databases, software and web-based tools. This information is needed to facilitate decision-making during the completion of a building's design, its construction and at the operational stages. Also, retrieval of the existing building rating systems was performed. Obstacles were clarified for the usage of the rating systems. The MCDM-23 (multi-criteria decision-making method) as a building's rating system was chosen, copied from Internet an installed into a personal computer. This program automates a multi-criteria evaluation. This paper/research performed an evaluation and comparison of two single-family house projects “Kedras” and “Vasaris”. It is found that the project “Kedras” is better than “Vasaris”.First Published Online: 26 Jul 2012